RRO: uma ontologia sobre o uso de requisitos de software em tempo de execução - Duarte, Bruno Borlini (2016)
In the last years, we have witnessed a growing interest in software systems that can monitor their environment and, if necessary, change their requirements in order to continue to fulfill their purpose. This particular kind of software usually consists of the main system responsible for the main functionality, along with a component that monitors the main system, analyzes the data collected and then,if necessary, reacts properly to make sure that the system continues to fulfill its requirements and executing its main functions in a proper way. There are many works in the literature that propose different solutions to this issue, such as adaptive or autonomic systems. However, there is not, in the scientific literature, a formal and explicit representation of what requirements at runtime are and what are the primary goals of their use. Still, in this context, most of the existing frameworks and methods that proposes their use have their own modeling languages and ways to represent, specify and make use of requirements at runtime. So, there is no common ground or a common sense about the use of requirements at runtime, thus resulting in a domain with overloaded concepts. This lack of consensus inside the presented domain and the problems caused by the lack of a formal and well-foundamented vocabulary about the domain were the main motivations for the execution of a systematic mapping (SysMap) about the methodologies that exists in the literature about requirements at runtime (RRT) and through the acquired, RRO (Runtime Requirements Ontology) was built.RRO is a domain reference ontology, grounded in UFO and built throuth SABiO framework to be a formal representation about the domain of RRT, providing a precise description about the entities that are part of the domain and establishing a commom vocabulary to be used for software engineers and stakeholders.